Symptom-level interactions between anxiety and internet addiction in Chinese adolescents: a large-scale network and residence difference analysis - Xie, Yi; Cheng, Xiao-Fei; Wang, Cong; Cai, Jia; Wang, Yu; Mu, Yun-Fei; Deng, Zhong-Yue; Deng, Ai-Ping; Song, Hong-Jun; Huang, Xue-Hua; Zhang, Lan; Zhang, Jun; et al. (Frontiers in Psychiatry, 2025)
BackgroundAnxiety and Internet addiction (IA) are prevalent and exhibit a strong correlation among adolescents. This study aimed to (a) identify key symptoms and relationships of the anxiety-IA combined network in Chinese adolescents and (b) examine the differences in anxiety-IA symptoms between rural and urban adolescents.MethodsThe study was a cross-sectional survey conducted in 122 secondary schools in Sichuan Province, China, using the Generalized Anxiety Disorder Scale and the Internet Addiction Test. General network analysis and bridge network analysis were used to identify the most influential symptoms and key connectors by adopting expected influence and bridge expected influence values. Network comparison tests were conducted to explore the global strength and network structure differences between rural and urban adolescents.ResultsThe study included 60,268 adolescents (mean age 15.90 ± 1.65 years; 54.44% females), stratified by residence: rural (n = 49,819) and urban (n = 10,449). In the general network, “Fantasize about being on the web” (IAT15), “Neglect household chores” (IAT2), and “Reluctant to be offline” (IAT16) were the most influential symptoms. Bridge network analysis revealed that “Use the web to escape from emotion” (IAT10), “Feeling afraid” (GAD7), and “Defensive or secretive about being on the web” (IAT9) served as key connectors that bridge the comorbid network of anxiety and IA. The network structure test detected residence-related differences, and the most influential and bridging symptoms diverged by residence. “Craving for next Internet use” (IAT11) and “Irritability” (GAD6) characterized rural adolescents, whereas “Excessive worry” (GAD3) and “Restlessness” (GAD5) typified urban adolescents.ConclusionsThis study offers new insights into the symptom-level interactions between anxiety and IA in adolescents. These findings also highlight the necessity of precisely addressing the comorbidity of anxiety and IA between rural and urban adolescents.